Evaluating the cost and wait-times of a task-sharing model of care for diabetic eye care: a case study from Australia. Issue 10 (5th October 2020) - Tahhan, Nina; Ford, Belinda Kate; Angell, Blake; Liew, Gerald; Nazarian, Joseph; Maberly, Glen; Mitchell, Paul; White, Andrew J R; Keay, Lisa
Abstract : Objectives: To determine whether a collaborative model of care that uses task-sharing for the management of low-risk diabetic retinopathy, Community Eye Care (C-EYE-C), can improve access to care and better use resources, compared with hospital-based care. Design: Retrospective audit of medical and financial records to compare two models of care. Setting: A large, urban tertiary Australian publicly funded hospital. Intervention: C-EYE-C is a collaborative care model, involving community-based optometrist assessment and 'virtual review' by ophthalmologists to manage low-risk patients. The C-EYE-C model of care was implemented from January to October 2017. Participants: New low-risk patient referrals with diabetes received at a tertiary hospital ophthalmology unit. Primary and secondary outcomes: Historical standard hospital care was compared with C-EYE-C for attendance, wait-times, outcomes and costs. Clinical concordance between the optometrist and ophthalmologist diagnosis and management was assessed using weighted kappa statistic. Results: There were 133 new low-risk referrals, managed in standard hospital care (n=68) and C-EYE-C (n=65). Attendance rates were similar between the models of care (72.1% hospital vs 67.7% C-EYE-C, p=0.71). C-EYE-C had shorter appointment wait-time (53 vs 118 days, p<0.01). In the C-EYE-C model of care, 68.2% of patients did not require hospital appointments and costs were 43% less than hospital care. There was substantial agreement between optometrists and ophthalmologists for diagnosis (κ=0.64, CI 0.47–0.81) and management (κ=0.66, CI 0.45–0.87). Conclusion: This Australian study showed that collaborative eye care resulted in reduced patient waiting times and considerable cost-savings, while maintaining a high standard of patient care compared with traditional hospital-based care in the management of low-risk hospital referrals with diabetic eye disease. The improved access and reduced costs were largely the result of better task allocation through greater utilisation of primary eye care professionals to provide services for low-risk patients. Better resource use may free up further resources for other eye care services.